Transcriptional and Posttranscriptional Regulation of Nitrogen-Responding Expression of Phosphoenolpyruvate Carboxylase Gene in Maize. - Suzuki, I. (1994)
To study the regulation of gene expression for enzymes in the C4 photosynthetic pathway of maize (Zea mays L.) in response to changing N status in developing photosynthetic cells, we have studied in vitro transcription of the phosphoenolpyruvate carboxylase (PEPC) gene in leaf nuclei isolated from plants during recovery from N starvation. The induction was specific for the C4-type PEPC gene (C4Ppc1), and its transcription was N dependent and increased markedly by supply of an N source, but there was a discrepancy between the steady-state levels of mRNA and the stimulation of in vitro transcription. The results suggest that the N-inducible expression of C4Ppc1 is regulated both transcriptionally and posttranscriptionally by N availability. The in vitro transcription rate of C4Ppc1 was greatly stimulated by incubating detached leaves with zeatin alone, whereas the rate remained essentially unchanged by incubating with an exogenous N source alone. The results, taken together, imply that cytokinins up-regulate the transcription of C4Ppc1 in response to N status, whereas glutamine and/or its metabolite(s) up-regulate the level of the transcript. The transcription was totally inhibited by cycloheximide, indicating that the cytokinin-dependent transcription of C4Ppc1 requires the synthesis of protein.